The contribution of antimicrobials and antimicrobial resistance to climate change and a possible way to reverse it whilst still offering high quality healthcare—a conceptual analysis - Jeanette Sams-Dodd; Frank Sams-Dodd (Frontiers in Public Health)
Since 1954, studies have consistently demonstrated that antimicrobials disrupt microbial environments, causing ecosystem degradation and release of greenhouse gases (GHG), making antimicrobials noteworthy climate stressors. Microbes created an atmosphere on Earth that supports eukaryotic life-forms and are essential for our normal physiological functions. However, despite their critical importance, microbes are mostly associated with infectious diseases, and antimicrobials are extensively used to eradicate them. In healthcare and veterinary medicine, antimicrobials are essential in fighting infections. The general risk associated with their use has focused on antimicrobial resistance and loss of efficacy, whereas their impact on microbial environments and GHGs has been overlooked. Using recent data, a single course of antibiotics is estimated to cause the release of 9.84 tonnes of CO2—the equivalent of a standard car driving around the Earth 1.47 times. Given the number of chemicals with antimicrobial effects, such an amount demands attention. Antibiotics, antiseptics, disinfectants, surfactants as well as pesticides, herbicides and many food additives all contribute to antimicrobial-resistance. Despite a focus on antibiotic stewardship, antimicrobials are still used indiscriminately, including where they fail to confer a critical or even demonstrable benefit. Using a One-Health approach, this manuscript provides a non-specialist introduction to the microbial environment and the impact of antimicrobials, and suggests how to minimise the environmental impact of healthcare whilst retaining quality care. Climate change is assumed to contribute to AMR, but this analysis finds that AMR strongly contributes to climate change, i.e., the reverse of the normal assumption. The current climate debate almost exclusively focuses on fossil fuel without in earnest considering other sources. However, without including the major, natural systems that significantly impact the climate, balanced informed decisions to mitigate the situation are impossible to make. By forcing the focus of the climate discussion onto only a narrow, limited set of explanations, the proposed solutions will likely not solve the main causes and their impact is therefore bound to be minimal. This is comparable to symptomatic versus curative treatment in healthcare. Whereas symptomatic treatment can help alleviate, it does not address the root cause and, therefore, cannot restore the patient to health.